Rhythms of Identity: A Comparative Study of Bertitik and Mongigol-Sumundai Music in Bajau Samah and Rungus Communities on Sabah's Northwest Coast, Malaysia - Mohd Hassan bin Abdullah, Mohd Azam bin Sulong, Mohd Nizam bin Nasrifan, Encik Suflan Faidzal Bin Arshad, Encik Nor Azman bin Haji Mohd Ramli (Tanjung Malim, 2024)
Rhythms of Identity: A Comparative Study of Bertitik and Mongigol-Sumundai Music in Bajau Samah and Rungus Communities on Sabah's Northwest Coast, Malaysia by Mohd Hassan bin Abdullah, Mohd Azam bin Sulong, Mohd Nizam bin Nasrifan, Encik Suflan Faidzal Bin Arshad, Encik Nor Azman bin Haji Mohd Ramli